Regional assessment of in vivo myocardial stiffness using 3D magnetic resonance elastography in a porcine model of myocardial infarction. Issue 1 (5th April 2017) - Arunachalam, Shivaram P.; Arani, Arvin; Baffour, Francis; Rysavy, Joseph A.; Rossman, Phillip J.; Glaser, Kevin J.; Lake, David S.; Trzasko, Joshua D.; Manduca, Armando; McGee, Kiaran P.; Ehman, Richard L.; Araoz, Philip A.
Abstract : Purpose: The stiffness of a myocardial infarct affects the left ventricular pump function and remodeling. Magnetic resonance elastography (MRE) is a noninvasive imaging technique for measuring soft‐tissue stiffness in vivo. The purpose of this study was to investigate the feasibility of assessing in vivo regional myocardial stiffness with high‐frequency 3D cardiac MRE in a porcine model of myocardial infarction, and compare the results with ex vivo uniaxial tensile testing. Methods: Myocardial infarct was induced in a porcine model by embolizing the left circumflex artery. Fourteen days postinfarction, MRE imaging was performed in diastole using an echocardiogram‐gated spin‐echo echo‐planar‐imaging sequence with 140‐Hz vibrations and 3D MRE processing. The MRE stiffness and tensile modulus from uniaxial testing were compared between the remote and infarcted myocardium. Results: Myocardial infarcts showed increased in vivo MRE stiffness compared with remote myocardium (4.6 ± 0.7 kPa versus 3.0 ± 0.6 kPa, P = 0.02) within the same pig. Ex vivo uniaxial mechanical testing confirmed the in vivo MRE results, showing that myocardial infarcts were stiffer than remote myocardium (650 ± 80 kPa versus 110 ± 20 kPa, P = 0.01). Conclusions: These results demonstrate the feasibility of assessing in vivo regional myocardial stiffness with high‐frequency 3D cardiac MRE. Magn Reson Med 79:361–369, 2018. © 2017 International Society for Magnetic Resonance in Medicine.